O cinema de Olney São Paulo: Grito da terra e o cinema nacional - Rios, Dinameire Oliveira Carneiro (2013)
This dissertation presents a critical study of the film Grito da terra (1964). Are analyzed elements of both ethical and aesthetic of the film within the context of Brazilian cinema in the decades 1950/60, based on the discourse of national-popular and adaptation processes undertaken by filmmaker Olney Sao Paulo for the production of Grito da terra from the novel by Ciro de Carvalho Leite. Discusses how the film of Olney São Paulo speaks to the productions of the season from ethical concerns in common, questioning how this work participates in debates raised by films that have the social problems of the northeast of Brazil as its central theme. As the film adaptation of a literary work are analyzed important aspects of dialogue between the book Grito da terra (1964) and the film in order to enhance important issues that are embedded in the process of adapting a literary work to the screen.